On the Principle of Scientific Objectivity, “Incorrect Analysis and Interpretation of Statistical Data” and the New Librarianship: a Reply to the Critical Response of E. A. Pleshkevich - V. K. Stepanov (Библиосфера)
This article is the author’s answer to the critical response of E. A. Pleshkevich on an article devoted to reducing the quantity of libraries in the Moscow region. Reasoned answers are given to the opponent’s three key objections. The point of view on the initial cause of the crisis in librarianship, which is the transfer of information flows to the digital sphere, is confirmed and specified. E. A. Pleshkevich’s understanding of the nature of the library as a public institution designed to guide reading is refuted. In response to the criticism of “incorrect analysis and interpretation of statistical data reflecting library construction in the Moscow region,” additional statistics are provided that irrefutably prove the absolute priority of the Moscow region in the liquidation of libraries throughout the Russian Federation. In response to the accusation of a biased assessment of the situation in the Moscow region, in which model libraries are being opened and various projects with big names are being implemented, it is pointed out that the most powerful indicator of the real state of affairs is the closure of 151 public libraries in the region from 2018 to 2022. Optimization through liquidation gives grounds for the conclusion that library reform in the Moscow region has completely failed.